Inhibition of ATP-regulated K(+)-channels by a photoactivatable ATP-analogue in mouse pancreatic beta-cells. - Ammälä, C; Bokvist, K; Galt, S; Rorsman, P (1991)
The effects of a photoactivable (DMNPE-caged) ATP-analogue on ATP-regulated K(+)-channels (KATP-channel) in mouse pancreatic beta-cells were investigated using the inside-out patch configuration of the patch-clamp technique. The caged precursor caused a concentration-dependent reduction of channel activity with a Ki of 17 microM; similar to the 11 microM obtained for standard Mg-ATP. The small difference in the blocking capacity between the precursor and ATP is probably the reason why no change in channel activity was observed upon photolysis of the caged molecule and liberation of ATP. It is suggested that the part of the ATP molecule involved in the blocking reaction of the KATP-channel is not sufficiently protected in DMNPE-caged ATP making this compound unsuitable for studying the rapid kinetics of ATP-induced KATP-channel inhibition.